FIRST REPORT OF Begomovirus INFECTION ON PAPAYA IN BENGKULU, INDONESIA - Sutrawati, Mimi; Parwito, Parwito; Priyatiningsih; Zarkani, Agustin; Sipriyadi; Sariasih, Yenny; Ganefianti, Dwi Wahyuni (Universitas Lampung, 2021)
First report of Begomovirus infection on papaya in Bengkulu, Indonesia. A field survey was conducted during 2019, wefound a severe systemic yellow mosaic, striped green mosaic on leaves petiole, green spots on the fruit of papaya, leafmalformation, and stunting symptoms on three papaya cultivation area in Rejang Lebong, Kepahiang, Bengkulu Tengah, andSeluma, Bengkulu Province, Indonesia. A begomo-like virus was inferred to be the possible cause of the virus-disease-likesymptoms. The study aimed to identify the causal of those typical symptoms on papaya. PCR using universal primer fortranscriptional activator protein (TrAp) and replication-associated protein (Rep) gene of Begomovirus successfully amplifiedthe DNA fragments of 900 bp in all 10 detected samples, except for samples with leaf malformation and stunting symptoms. Itis indicating that those typical symptoms on papaya is associated with Begomovirus infection, while the causal of leafmalformation and stunting is unknown yet. This work is the first report of Begomovirus infected papaya in Indonesia. Severedisease incidence caused by this pathogen was observed on papaya plants in Bengkulu Province that was in the range of 42–100%. This finding is a precious information to be used for identification, and characterization the species of the virus,determining control strategies against the disease.